Aid for trade in Asia and the Pacific promoting connectivity for inclusive development. (Metro Manila, Philippines Asian Development Bank, 2017)
This report highlights emerging trends in AfT in the context of evolving trade performance in Asia and the Pacific. In particular, the impact of AfT on trade in services, thereby helping increase economic and job opportunities for women, and the rise of ecommerce. The report ends by considering policy implications of the experiences of geographically challenged economies of the region along the dimensions of trade costs, AfT, trade in services, and the role of the digital economy.
Keywords: Economic policy -- Pacific Area; Economic conditions -- Pacific Area; Electronic books